PERBANDINGAN SISTEM KONTRAK BERBASIS KINERJA ATAU PERFORMANCE BASED CONTRACT (PBC) DAN KONTRAK TRADISIONAL - WIBOWO, BAYU (KURVA S JURNAL MAHASISWA, 2014)
Based on the problems found, the comparison system How Performance Based Contracts or Performance Based Contract (PBC) and the Traditional Contract. The aim of this study was to Knowing comparison system Performance Based Contracts or Performance Based Contract (PBC) and the Traditional Contract.               Contract or agreement is an event in which a promise to another person or in which two people were each promised to carry out a casePerformance Based Contract (PBC) is a contract relating to the implementation of the construction or production of a physical form other to achieve or maintain suatau specific performance set forth in a specific time period, covering the design work, construction, and maintenance services are carried out in an integrated manner to ensure the achievement of kenerja seabagaimana specified in the performance specification.               Traditional contract is where the owner will be in touch with several contractors to complete the project.From the discussion, Based on the SWOT matrix, it can be concluded that the contract Berbasis  Kinerja atau Performance Based Contract (PBC) is more beneficial for service users to determine the planning, management processes and methods of work most efficiently.               Traditional contract will provide a threat to the owner if the construction undertaken construction failure because all the construction problems (either a designer or design revision) will be covered by the owner.